Trust Me, I Believe in God: Candidate Religiousness as a Signal of Trustworthiness. (November 2016) - Clifford, Scott; Gaskins, Ben
Religion plays a prominent role in American politics, and candidates often attempt to display their religiousness in a variety of ways. For example, in spite of the association between conservatism and religion, research shows that candidates of both parties routinely use religious language and seek to demonstrate personal religiousness. Existing research portrays religious rhetoric primarily as an ideological cue, failing to explain why Democrats would make religious appeals. Drawing on psychological theories of prejudice toward atheists, we argue that candidates emphasize their religiousness in order to enhance perceptions of their trustworthiness and morality. Using survey data, we show that voters are quite unlikely to support an atheist candidate, an effect that is strongly driven by the perception of atheists' morality. Next, we show evidence that voters perceiving Hillary Clinton as religious also viewed her as more trustworthy, and were more likely to view her favorably. Finally, we show experimentally that religious candidates are perceived as more trustworthy, at least among a wide swath of the electorate. We conclude that displays of religiousness likely serve not only an ideological purpose but also the broader goal of increasing perceived candidate trustworthiness.